DESIGN OF ETHNOMATHEMATICS MOBILE MODULE TO FACILITATE STUDENTS MATHEMATICAL THINKING ABILITY - Henry Suryo Bintoro; Ratri Rahayu; Alif Catur Murti (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The ability to think mathematically is very important for students to solve problems in everyday life. However, in reality, many students cannot find concepts, reason, problem-solving, communication, and connect mathematics to other sciences. This happens because students are not able to understand abstract mathematics. Teaching materials are needed in the form of applications on the device so that they are attractive to students. The ethnomathematics mobile module is a teaching material that contains mathematical material that is brought closer to everyday life through ethnomathematical learning. This study uses research and development (R&D) methods with the Borg & Gall model which is adapted from Sugiono's development model. The data of this study were obtained from a validation questionnaire of material experts and media experts. The type of data produced is qualitative data which is analyzed with assessment criteria guidelines to determine product quality. The purpose of this study is to obtain an ethnomathematics mobile module design to facilitate valid mathematical thinking skills. Based on the results of the assessment from the validator, the average value of the ethnomathematics mobile module material validity test was 3.76 (very valid) by material experts and the validity of the ethnomathematics mobile module media was 3.80 (very valid) by media experts. These results indicate that the ethnomathematics mobile module that was developed is valid or feasible to use.